Global Trends and Collaboration in Community-Based Learning and Civic Engagement Research in Higher Education: A Bibliometric Analysis of 2015-2025 - Mariyani Mariyani; Aim Abdulkarim; Rahmat Rahmat; Kokom Komalasari; Nadiyah Dzatul Izzah (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
This study investigates global trends and collaboration patterns in Community-Based Learning (CBL) and Civic Engagement (CE) research in higher education between 2015 and 2025, focusing on fragmented civic engagement practices, limited student participation, and weak university–community partnerships as the central rationale. Employing a bibliometric approach, 110 Scopus-indexed publications were examined using VOSviewer and Publish or Perish to identify publication trajectories, influential authors, productive institutions, and emerging thematic clusters. Results indicate steady growth in research outputs, with peaks in 2023–2024, and journal articles as the primary dissemination medium. The United States emerges as the largest contributor, followed by India, South Africa, and the United Kingdom. Keyword analysis highlights five thematic clusters: civic engagement, interdisciplinarity, health, sustainability, and community capacity building. These findings reveal regional disparities and emphasize the importance of digital integration and stronger collaboration among universities, communities, and students to advance inclusive and transformative civic learning.